Safety and efficacy of ketamine use in patients with vaso‐occlusive crisis: A systematic review and meta‐analysis - Ernesto Calderon Martinez; Stephin Zachariah Saji; Thomas Campos Carmona; Vaidarshi Abbagoni; Mohammad Salman; Mishell Estefanía Llerena Vargas; Suchita Mylavarapu; Druvini Fernando; Lakshmi Sheethal Arvapalli; Nathalia Schettino Samad; Nithin Karnan; Camila Sanchez Cruz (eJHaem, 2024)
Abstract Introduction Sickle cell disease (SCD) is characterized by acute episodes called vaso‐occlusive crises (VOC). VOC is marked by severe pain due to blocked blood vessels by sickled cells. Ketamine has been reported to be effective and safe in managing VOC in SCD patients. Objectives/methods This review aims to determine ketamine's safety and efficacy through analysis of clinical trials and observational studies. Methods Adhering to PRISMA guidelines, this systematic review and meta‐analysis systematically searched seven databases on May 20, 2024 for randomized control trials (RCT), cohorts, and case–control studies. Results Five studies with 689 participants met the inclusion criteria. A meta‐analysis of two studies (518 observations) for the Numerical Rating Scale (NRS) pain score showed no significant difference, with a standardized mean difference (MD) of 0.23 (95% CI: −0.13 to 0.59, p = 0.21, I2 = 0%). For morphine milligram equivalent (MME), a meta‐analysis of two studies (344 observations) resulted in an MD of −0.03 (95% CI: −0.09 to 0.04, p = 0.45, I2 = 97%). However, the side effects analysis from four studies (608 observations) showed a significantly higher relative risk (RR) of 5.74 (95% CI: 2.80–11.79, p < 0.0001, I2 = 0%) for mild side effects, including nausea, vomiting, and dizziness. Conclusion Ketamine qualitative synthesis shows potential for improving pain management in SCD patients during VOC, but without statistically significant differences in pain reduction. It is associated with increased mild side effects, though no severe adverse events were reported. Further research is needed to increase the sample size and power of the analysis to clarify optimal dosing and administration protocols for ketamine in this context.